A new perspective of lanthanide metal–organic frameworks: tailoring Dy-BTC nanospheres for rechargeable Li–O2 batteries - Liu, Dan; Zhang, Xinmin; Yan-Jie, Wang; Song, Shuyan; Cui, Lifeng; Fan, Hongbo; Qiao, Xiaochang; Fang, Baizeng (Nanoscale, 2020)
Nanoscaled lanthanide metal–organic frameworks (NLn-MOFs) have emerged as attractive nanomaterials for photofunctional applications. To enhance the inherent properties and endow NLn-MOF materials with desired electrochemical performance for rechargeable Li–O2 batteries, rational design and synthesis of NLn-MOFs with tailored morphologies for high O2 accessibility and rich open metal sites to bind O2 molecules is highly desired and remains a grand challenge. Herein, we prepare Dy-BTC nanospheres, which are explored for the first time as an O2 cathode in Li–O2 batteries. Interestingly, the specific capacity and electrochemical stability of the Dy-BTC nanosphere-based electrode outperform significantly those of the bulk crystalline Dy-BTC. A full discharge capacity of 7618 mA h g−1 at 50 mA g−1 has been achieved by the Dy-BTC nanospheres. Furthermore, the Dy-BTC nanospheres stably deliver a discharge capacity of 1000 mA h g−1 at 200 mA g−1 for 76 cycles, which is remarkably longer than that of the bulk crystalline Dy-BTC with a cycling life of 26 cycles.